Problems in entrepreneurial potential development: a comprehensive analysis of contemporary barriers and challenges - Baxtiyor , Xabibullayev (GREEN ECONOMY AND DEVELOPMENT, 2025)
This study explores the primary obstacles that hinder the development of entrepreneurial potential in modern economic systems. Using a combination of systematic literature review and case study methods, the research identifies critical barriers such as limited access to finance, weak educational infrastructure, regulatory hurdles, and socio-cultural impediments. The findings show that financial limitations affect 67% of aspiring entrepreneurs, followed by insufficient mentorship (54%) and complex legal regulations (48%). The article concludes with strategic recommendations aimed at governments, educational bodies, and entrepreneurial support institutions.